FACTOR ANALYSIS OF THE INFLUENCE OF LIFE APPERCEPTION ON TIKTOK’S CONTENT CREATORS IN CHINA - ZhiYing, Jin; Iskandar, Hari; Marta, Rustono Farady (Interaksi: Jurnal Ilmu Komunikasi, 2024)
The Tiktok application became the largest amount of account around the world nowadays. As the rapid increase of Tik tok users, the more and more users try to create their own world through the platform. The study explores the ability creators of content gainess through Uses and Gratification Theory and Self-determination Theory, using the quantitative approach with survey method by 305 purpose samples. The article concludes that content creators of Tiktok users could promote the ability to perceive life through self-expression and creation consciousness. These research values contribute to two sides: On the one hand, the difference between passive recipients and content creators is revealed through complex and detailed data analysis, which aims to encourage more users not only to be passive recipients, but to try to imitate and seek new content through the social media application. Especially those who want to improve or even change their personal characteristics. On the other hand, the article provides a new perspective to explore Tik tok users in depth, which could be useful for other social media researches.